The hypertension of the inferior vena cava (experimental work): endovascular-interstitial reflectivity of venous origin - Stajano, Carlos; Scandroglio, J J (Cirugía del Uruguay, 2020)
The acute ligation of the inferior vena cava in hte dog causes reflex vaso-constriction in the vasa-vasorum irrigating the wall of the vein